Clinical case of focal epilepsy due to non-traumatic intracranial hemorrhage - Alina A. Seryogina; Artem E. Khmelevsky (LLC "MEDIAFORMAT", 2024)
Epilepsy is a multifactorial disease, the important role in the emergence and development of which is played by hereditary factors, exogenous causes, combined effects of the exogenous causes and congenital or acquired susceptibility. Perinatal (antenatal, natal, and early postnatal) damage to the central nervous system is a common etiological factor of epilepsy in children. The paper reports the clinical case of the patient having structural focal epilepsy with bilateral tonic seizures, cramps resulting from the non-traumatic intracranial hemorrhage.